Comparative SWOT analysis for water solutions in Asia and Africa - Nagara, Genia; Lam, Wei Haur; Lee, Nasha Chia Hwee; Othman, Faridah; Shaaban, Md Ghazaly (Springer Verlag, 2015)
Various scientific and technological based solutions such as virtual water trading, desalination, groundwater extraction and wastewater reuse have been proposed and implemented in many parts of Asia and Africa to relieve water scarcity. This paper applies SWOT (strengths, weaknesses, opportunities and threats) analysis to examine the suitability of these alternative water solutions to alleviate water scarcity. SWOT analysis proves to be a useful decision making tool as it provides a qualitative approach to simplify multilayer and interdisciplinary problems. The main input for the SWOT analysis consists of knowledge gathered from seven experts in the field of water and environmental sciences. The results show that compared to other solutions, wastewater reuse offers the most desirable qualities as a viable water solution for sustainable water management in Asia and Africa.